Evaluation of Financial and Maqasid Syariah Performance of Islamic Banks in Southeast Asia (2019–2023) - Fatih Fuadi; Suhendar Suhendar; Hanif Hanif; Wahyu Iryana; Anas Malik (Khazanah Sosial, 2025)
This study aims to analyse the performance of Islamic banks in Southeast Asia through a comprehensive framework that includes both financial and non-financial aspects, particularly those grounded in the Maqasid al-Shari’ah. The research is significant as the rapid growth of Islamic finance in the region has not been matched by systematic performance evaluations. Employing a quantitative approach with an explanatory design, data were collected from financial reports, structured surveys, and interviews, and analysed using panel data regression with the Fixed Effect Model (FEM). The findings reveal a significant post-pandemic recovery among Islamic banks, demonstrated by improvements in profitability, operational efficiency, and asset quality. The Maqasid Syariah Index (MSI) shows varied achievements, with Malaysia and Indonesia leading in the integration of Islamic ethical and social values. Internal factors such as bank size and age, along with external factors such as GDP growth, the Islamic Financial Development Index (IFDI), and Sharia Governance Score (SGS), significantly influence performance. These results underscore the importance of aligning macroeconomic factors, Islamic governance, and financial infrastructure to support the resilience and sustainability of Islamic banking. This study offers an original contribution by developing a performance evaluation model rooted in maqasid principles and provides policy recommendations to enhance the integration and efficiency of the regional Islamic financial system.